Soil-induced impacts on forest structure drive coarse woody debris stocks across central Amazonia - Martins, Demétrius L.; Schietti, Juliana; Feldpausch, Ted R.; Luizão, Flávio Jesus; Phillips, Oliver L.; Andrade, Ana C.S.; Castilho, Carolina Volkmer; Laurance, Susan G.W.; Oliveira, Átila Cristina Alves de; Amaral, Iêda Leão do; Toledo, Jos? Julio; Lugli, Laynara F.; et al. (Plant Ecology and Diversity, 2015)
Background: Coarse woody debris (CWD) is an essential component in tropical forest ecosystems and its quantity varies widely with forest types. Aims: Relationships among CWD, soil, forest structure and other environmental factors were analysed to understand the drivers of variation in CWD in forests on different soil types across central Amazonia. Methods: To estimate CWD stocks and density of dead wood debris, 75 permanent forest plots of 0.5 ha in size were assessed along a transect that spanned ca. 700 km in undisturbed forests from north of the Rio Negro to south of the Rio Amazonas. Soil physical properties were evaluated by digging 2-m-deep pits and by taking auger samples. Results: Soil physical properties were the best predictors of CWD stocks; 37% of its variation was explained by effective soil depth. CWD stocks had a two-fold variation across a gradient of physical soil constraints (i.e. effective soil depth, anoxia and soil structure). Average biomass per tree was related to physical soil constraints, which, in turn, had a strong relationship with local CWD stocks. Conclusions: Soil physical properties appear to control average biomass per tree (and through this affect forest structure and dynamics), which, in turn, is correlated with CWD production and stocks. © 2014, © 2014 Botanical Society of Scotland and Taylor & Francis.